2019
DOI: 10.3389/fphys.2019.00099
|View full text |Cite
|
Sign up to set email alerts
|

VasoTracker, a Low-Cost and Open Source Pressure Myograph System for Vascular Physiology

Abstract: Pressure myography, one of the most commonly used techniques in vascular research, measures the diameter of isolated, pressurized arteries to assess the functional activity of smooth muscle and endothelial cells. Despite the widespread adoption of this technique for assessing vascular function, there are only a small number of commercial systems and these are expensive. Here, we introduce a complete, open source pressure myograph system and analysis software, VasoTracker, that can be set-up for approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…In some experiments, Ca 2+ signals were calibrated using Ca 2þ Images were acquired at 10 or 5 Hz (consistent within each experimental protocol) using an upright fluorescence microscope equipped with a 16× objective lens (0.8 NA; Nikon, Tokyo, Japan) and large format (1,024 × 1,024; 13-μm pixels) back-illuminated electronmultiplying charge-coupled device camera (iXon 888; Andor, Belfast, UK) and stored for offline analysis. An edge-detection algorithm (Lawton et al, 2019) was used to track the width of arteries in image recordings. The algorithm extracts an intensity profile along a scanline orientated perpendicular to the longitudinal axis of the vessel.…”
Section: Extraction and Analysis Of Endothelial Ca 2+ Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some experiments, Ca 2+ signals were calibrated using Ca 2þ Images were acquired at 10 or 5 Hz (consistent within each experimental protocol) using an upright fluorescence microscope equipped with a 16× objective lens (0.8 NA; Nikon, Tokyo, Japan) and large format (1,024 × 1,024; 13-μm pixels) back-illuminated electronmultiplying charge-coupled device camera (iXon 888; Andor, Belfast, UK) and stored for offline analysis. An edge-detection algorithm (Lawton et al, 2019) was used to track the width of arteries in image recordings. The algorithm extracts an intensity profile along a scanline orientated perpendicular to the longitudinal axis of the vessel.…”
Section: Extraction and Analysis Of Endothelial Ca 2+ Signalsmentioning
confidence: 99%
“…Diameter measurements of pressurized arteries were performed using the VasoTracker open source pressure myograph system (system (RRID:SCR_017233; Lawton et al, 2019). Mesenteric arteries were dissected free from surrounding tissue, cleaned of connective tissue, and mounted on similar sized glass pipettes in a VasoTracker pressure myograph chamber.…”
Section: Pressure Myographymentioning
confidence: 99%
“…Outside diameter recording was used simultaneously with servo-null micropressure measurement to test and validate our method; however, we also confirmed that inner diameter tracking gave comparable results. We used outside over inner diameter tracking because outside diameter tracking can easily be achieved using various already available, open-source tools: VasoTracker (Lawton et al 2019), ImageJ, etc. In addition to reporting novel findings on valve function/dysfunction in lymphatic valves from Foxc2 Cre/+ and Prox1-CreER T2 ;Cx43 fx/fx ;Cx37 −/− mice, the significance of this work comes in making available a more accessible technique for quantitative measurement of lymphatic valve function.…”
Section: Discussionmentioning
confidence: 99%
“…First-order mesenteric vessels were selected as a widely used model of vascular and endothelial function since there is a wealth of published background information to aid experimental design and data interpretation. For pressure myograph experiments, we used the open source pressure myograph system, VasoTracker [49] and recorded outer vessel diameter in response to various treatments at 70 mmHg and 37°C. For Ca 2+ imaging experiments, arteries were opened longitudinally, and endothelial cells were preferentially loaded with the Ca 2+ indicator, Cal-520/AM (5 μM).…”
Section: Experimental Techniquesmentioning
confidence: 99%